2020
DOI: 10.1021/acs.chemmater.9b04287
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Enhancement Mechanism of A-Site-Deficient LaxNiO3 as an Oxygen Redox Catalyst

Abstract: Lanthanide perovskite oxides have attracted much attention as an oxygen reduction and evolution catalyst because of their high chemical stability and composition adjustability. A defect strategy has been applied to enhance their electrocatalytic activity with the modulation of the crystal/electronic structure. However, the intrinsic roles of the defects, particularly A-site vacancies, are poorly understood. Herein, we prepare La x NiO 3 with various ratios of A-site vacancies by a facile nonstoichiometric stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 79 publications
2
52
0
Order By: Relevance
“…A cutoff energy of 500 eV was adopted for the simulation. Structure relaxation proceeded until all forces on atoms were less than 1 meV Å −1 and the total stress tensor was within 0.01 GPa of the target value, as in a previous study 50 . In order to accurately describe the electronic structure of the transition metal, the DFT + U approach was used, assuming U values for Mn- 3d , Ni- 3d , and Zr- 4d of 6.0, 7.4, and 4.0 eV, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A cutoff energy of 500 eV was adopted for the simulation. Structure relaxation proceeded until all forces on atoms were less than 1 meV Å −1 and the total stress tensor was within 0.01 GPa of the target value, as in a previous study 50 . In order to accurately describe the electronic structure of the transition metal, the DFT + U approach was used, assuming U values for Mn- 3d , Ni- 3d , and Zr- 4d of 6.0, 7.4, and 4.0 eV, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…What is more, to verify the effect of V La caused by urea addition on performance improvement, we designed several comparison experiments. It was found that only by reducing the dosage of La 3+ in preparation may result in the formation of oxygen vacancies as well as unstable LMO structure [9–12] . More importantly, the activity improvement in model toluene oxidation of such approach is very limited as shown in Figure S32.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the introduction of A‐site deficiencies into the lattice structure of perovskites can significantly alter the catalytic performance in oxygen‐related reactions [8] . For example, A‐site defects generated by nonstoichiometric strategy could boost the catalytic activity of LaFeO 3 , [9] (BS) 1− x CF, [10] double perovskites PrBa 1− x Co 2 O 5+ δ [11] and La x NiO 3 [12] in oxygen reduction reaction (ORR), and the phenomena were attributed to the creation of surface oxygen vacancies ( V O ). Moreover, the preferential generation of cation vacancies on SnCoFe perovskite by Ar plasma treatment resulted in high exposure of B‐site metal and improved catalytic activity for OER [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Besides the stoichiometric A‐site substitution, the A‐site nonstoichiometry, in either A‐site deficient or A‐site excessive materials, can also effectively tune the catalytic performance of perovskite oxides. [ 74 ] For example, the A‐site deficient La 1−x FeO 3− δ presented excellent ORR activity at x = 0.05, which mainly followed the 4‐electron transfer process. It was proposed to be attributed to the increased content of oxygen vacancies and the formation of Fe 4+ /Fe 3+ couple.…”
Section: Strategies To Design Perovskite Oxides For Catalyzing Orrmentioning
confidence: 99%